2016
DOI: 10.1016/s1473-3099(16)30208-0
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to optimise the care continuum for chronic viral hepatitis: a systematic review and meta-analyses

Abstract: World Health Organization and US Fulbright Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
123
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(128 citation statements)
references
References 82 publications
4
123
0
1
Order By: Relevance
“…Potential strategies to improve HCV testing include education and counseling by health professionals with on-site HCV testing (Cullen et al, 2006; Lacey, Ellen, Devlin, Wright, & Mijch, 2007; Meyer et al, 2015; Rosenberg et al, 2010; Sahajian et al, 2011; Zhou et al, 2016), physical and electronic medical chart reminders to prompt targeted risk-based assessment and testing (Drainoni et al, 2012; Krauskopf et al, 2014; Litwin et al, 2012; Meyer et al, 2015; Zhou et al, 2016), and simplified testing, including dried blood spot testing (Abou-Saleh, Rice, & Foley, 2013; Coats & Dillon, 2015; Craine, O'Toole, D'Arcy, & Lyons, 2009; Hickman et al, 2008; McLeod et al, 2014; Meyer et al, 2015; Tait, Stephens, McIntyre, Evans, & Dillon, 2013; Zhou et al, 2016), and point-of-care HCV testing (Beckwith et al, 2016; Bottero et al, 2015; Morano et al, 2014). …”
Section: Hcv Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential strategies to improve HCV testing include education and counseling by health professionals with on-site HCV testing (Cullen et al, 2006; Lacey, Ellen, Devlin, Wright, & Mijch, 2007; Meyer et al, 2015; Rosenberg et al, 2010; Sahajian et al, 2011; Zhou et al, 2016), physical and electronic medical chart reminders to prompt targeted risk-based assessment and testing (Drainoni et al, 2012; Krauskopf et al, 2014; Litwin et al, 2012; Meyer et al, 2015; Zhou et al, 2016), and simplified testing, including dried blood spot testing (Abou-Saleh, Rice, & Foley, 2013; Coats & Dillon, 2015; Craine, O'Toole, D'Arcy, & Lyons, 2009; Hickman et al, 2008; McLeod et al, 2014; Meyer et al, 2015; Tait, Stephens, McIntyre, Evans, & Dillon, 2013; Zhou et al, 2016), and point-of-care HCV testing (Beckwith et al, 2016; Bottero et al, 2015; Morano et al, 2014). …”
Section: Hcv Testingmentioning
confidence: 99%
“…Although finger-stick dried blood spot testing enhances HCV testing (Abou-Saleh, et al, 2013; Coats & Dillon, 2015; Craine et al, 2009; Hickman et al, 2008; McLeod et al, 2014; Meyer et al, 2015; Tait et al, 2013; Zhou et al, 2016), collection cards need to be sent somewhere for testing at centralized diagnostic laboratories requiring people to come back for a second visit to receive their result. Among HIV-infected gay and bisexual men, innovative approaches using on-line ordering with self-collected dried blood spot testing simplifies testing and improves access to marginalized populations (Terrence Higgins Trust, 2016).…”
Section: Hcv Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, developing a standardised monitoring approach for interventions including diagnosis and treatment along the continuum of care, which is already established for HIV, could now be considered for hepatitis B and C. A recent review of operational interventions along the chronic viral hepatitis care continuum for people with diagnosed or undiagnosed chronic viral hepatitis demonstrated that a range of relatively simple, inexpensive operational interventions can substantially improve engagement and retention along the cascade of care, thereby optimising the implementation of screening, care, and treatment programmes [31]. …”
Section: The European Situationmentioning
confidence: 99%
“…It was also mentioned by some patients that they are not comfortable to receive HCV treatment at OST clinics . In a systematic review, it was demonstrated that co‐location of HCV treatment with mental health and addiction services cannot significantly improve the treatment uptake . Treatment uptake between 0% and 60% (median 30%) was reported among PWID and between 24% and 76% (median 55%) among PWID plus additional criteria, for example HCV genotype or drug use status .…”
Section: Discussionmentioning
confidence: 99%